2007
DOI: 10.1080/02652040701547658
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of sol-gel mesoporous silica materials providing a slow release of doxorubicin

Abstract: Samples of mesoporous base-catalysed silica xerogel materials made by the sol-gel process were impregnated with an anticancer drug--doxorubicin, followed by different times of ageing at room temperature. The effect of ageing time on the physical and structural properties as well as sorption-desorption of the drug was investigated. The obtained results suggest an inverse relationship with a solid density and surface area increasing as the pore size and volume decrease during ageing time. These results also reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Therefore, it is desired to explore a new drug hosting system that can produce amorphous APIs with acceptable stability and shelf life. The discovery of a series of new ordered mesoporous silica material, which has a regular pore size distribution that can be systematically varied between 2 and 30 nm, has opened up new possibilities in pharmaceutical applications 14–17. Surface functionalized mesoporous MCM‐41 were investigated for controlled release of various APIs 18–20.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is desired to explore a new drug hosting system that can produce amorphous APIs with acceptable stability and shelf life. The discovery of a series of new ordered mesoporous silica material, which has a regular pore size distribution that can be systematically varied between 2 and 30 nm, has opened up new possibilities in pharmaceutical applications 14–17. Surface functionalized mesoporous MCM‐41 were investigated for controlled release of various APIs 18–20.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption of Dox was studied by Prokopowicz and coworkers on mesoporous xerogels with non-uniform pores (Prokopowicz and Przyjazny, 2007) as well as on mesoporous silica microparticles with ordered structure of uniform pores (Prokopowicz et al, 2016). It was found that interaction of positively charged doxorubicin hydrochloride with negatively charged silica centers (pH 6.6) leads to the drug adsorption on the surface of larger pores and its subsequent diffusion into the smaller ones.…”
Section: Introductionmentioning
confidence: 99%
“…In order to minimize undesired damages of healthy cells without reducing therapeutic action of Dox, drug carrier systems are widely used (Aznar et al, 2011;Bernardos et al, 2010;Chen et al, 2013;Gao et al, 2011;Gu et al, 2012;Hu et al, 2013;Knezevic et al, 2011Knezevic et al, , 2013Lee et al, 2010Lee et al, , 2011Maeda et al, 2003;Meng et al, 2010;Mishra et al, 2014;Nishiyama and Kataoka, 2003;Prokopowicz and Przyjazny, 2007;Prokopowicz et al, 2016;Safari and Zarnegar, 2014;Singh et al, 2011;Tan et al, 2011;Wang et al, 2011;Yang et al, 2008;Yokoyama, 2011;Yuan et al, 2011;Zhang et al, 2011). Among them, ordered mesoporous silicas of MCM-41 type are the most promising solid supports for the formation of biologically active systems (Aznar et al, 2011;Bernardos et al, 2010;Gu et al, 2012;Hu et al, 2013;Knezevic et al, 2011Knezevic et al, , 2013Lee et al, 2010Lee et al, , 2011Meng et al, 2010;Prokopowicz et al, 2016;Yuan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…At the physiological buffer (pH around 7.4), the silanol groups (Si-OH) and -COOH in the nano carriers would become deprotonated, and a strong electrostatic repulsion between the negative charges of (SiO -and -COO -groups) and the negative charge of naproxen molecule would be generated. Consequently, the pH value of 7.4 promotes the release rate [16][17][18][19][20]. However, the residual drug molecules can be occluded in the channels which would restrict achieving achieve the overall release.…”
Section: In Vitro Release Studiesmentioning
confidence: 97%